Optimal measurement location of on-site based CT-derived FFR on midterm prognosis. (14th October 2021) - Okada-Nozaki, Y; Fujimoto, S; Aoshima, C; Kamo, Y; Okano-Kawaguchi, Y; Takamura, K; Kudo, A; Takahashi, D; Hiki, M; Dohi, T; Okazaki, S; Tomizawa, N; et al.
Abstract: Background: Fractional Flow Reserve (FFR) derived from coronary computed tomography angiography (CCTA) enables anatomical and hemodynamical assessment of coronary artery disease. CT-FFR, which can be acquired on-site workstation using fluid structure interaction during the multiple optimal diastolic phase, has an incremental diagnostic value over conventional CCTA. However, few studies are focused on investigating the appropriate measurement location of CT-FFR, considering the prognosis, using CCTA as a standalone modality. Purpose: The aim of this study is to assess the clinical impact on CT-FFR with an appropriate measurement. Methods: A total of 370 consecutive patients who underwent CCTA in a single-heartbeat scan with a phase window of 70% to 99% of the R-R interval, showing 50–90% stenosis of at least one major epicardial vessel measuring ≥1.8 mm in diameter on CCTA were retrospectively analyzed and followed during a median follow up 2.9 years. CT-FFR values were measured at three points: 1, 2 cm distal to a target lesion (CT-FFR1cm, 2cm) and the vessel terminus (CT-FFRlowest), and a CT-FFR value ≤0.80 was considered abnormal. The endpoint was MACE, a composite of cardiac death, non-fatal MI, and unplanned revascularization. Results: The incidence of MACE occurred in 8.4% (31/370) of the whole patients, including four cardiac deaths, ten all cause deaths, two non-fatal MI, and twenty unplanned revascularization. The Kaplan-Meier survival analysis demonstrated a significantly higher cumulative MACE rate in patients with positive CT-FFR1cm and 2cm than those with negative CT-FFR1cm and 2cm, while there was no significant difference between negative and positive in CT-FFRlowest, among patients with negative CT-FFR1cm and 2cm (Figure 1). Among 221 patients, who did not perform early revascularization within 90 days from CCTA, there was no significant difference in CT-FFRlowest in the incidence of MACE. In contrast, the risk of MACE was significantly higher in both positive CT-FFR1cm and CT-FFR2cm (Figure 2). Conclusion: From a view point of clinical outcome for patients with moderate to severe stenosis on CCTA, a CT-FFR value when measured at 1-to-2 cm distal to a target lesion could be feasible for the deferral of unnecessary invasive coronary angiography safely. Moreover, CT-FFR1–2cm showed better risk stratification measurement rather than CT-FFRlowest, based on future adverse cardiac event. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Canon Medical Systems Corporation